Physicochemical, microbial and ecotoxicological characteristics of textile effluent collected in the southeast region of Brazil - Mainardi, Pedro Henrique [UNESP]; Bidoia, Ederio Dino [UNESP] (Macrothink Institute, 2019)
The textile sector comprises several segments and detain a great economic and social value. Textile industries, however, demands large amounts of water and generate great loads of effluent in their production process. The effluent’s physical and chemical parameters, as much as its microbiological and ecotoxicological aspects, has been extremely useful to find out the key aspects for the development of novel methods of treatment and implementation of new techniques of industrial processing. In this study, a real effluent sample was collected from a textile factory situated in the southeast region of Brazil and analyzed for turbidity, solids content, oils and greases, alkalinity, pH value, electrical conductivity, BOD, COD, organic and inorganic components, total viable bacteria, coliforms and EC50 ecotoxicological degree using the microcrustacean Daphnia magna and the lettuce Lactuca sativa. The measured parameters were seen to have a great variation in comparison to a vast literature report and the characterization was shown to be extremely important in the search of new methods to reduce the volume and the toxicity of this kind of effluent.
Keywords: Sewage - Analysis; Biological monitoring; Pollution; Cleaning and dyeing industry